The double burden of malnutrition and environmental enteric dysfunction as potential factors affecting gut-derived melatonin in children under adverse environments - Alane N. Bezerra; Alane N. Bezerra; Caroline L. Peixoto; Synara C. Lopes; Veralice M. S. Bruin; Pedro Felipe C. Bruin; Reinaldo B. Oriá (Frontiers in Nutrition, 2023)
Graphical AbstractPoor environmental conditions combined with continuous unhealthy and unsafe diets may substantially increase the risk of a vicious cycle of enteric infections (EED–environmental enteric dysfunction) and malnutrition (DBM–double burden of malnutrition) in children. Gut melatonin, mainly produced by the intestinal microbiota, can modulate the composition, variety, and dynamics of the microbiota itself and may affect and be affected by intestinal microbiota alterations due to DBM and EED.